Striving towards independent living: the trials and tribulations of institutionalised adolescents in Malaysia - Mohd munir, Nur Syuhada; Rais, Haniza; Zubairi, Ainol Madziah (IIUM Press, 2024)
This phenomenological study explores how five institutionalised Malay adolescents used adaptive strategies towards independent living upon being released from welfare institutions. Five 17-year-old Malay Muslim adolescents, three males and two females, were recruited via purposive sampling for a focus group discussion to gather insights into their plans and strategies to cope with life challenges after being released from their respective welfare institutions. Thematic analysis of the FGD data extracted six themes that portrayed the adolescents’ adaptive strategies for facing challenges in life. The themes include making personal preparations, acquiring personal strengths, setting a career direction, exploring the support of friends and outsiders, feeling of being complete, searching for personal necessities and having a sense of responsibility. The findings highlight the need for developing a comprehensive life skills intervention for institutionalised adolescents and psychoeducation counselling modules to alleviate the adolescents’ uncertainties in going through the adjustment phase outside welfare institutions.